2020
DOI: 10.1093/mnras/staa3631
|View full text |Cite
|
Sign up to set email alerts
|

The age of the carina young association and potential membership of HD 95086

Abstract: Carina is a nearby young stellar association. So far, only a small number of stars have been clearly identified as members of this association. In this paper we reanalyse the membership of the association in light of Gaia DR2 data, in particular finding that HD 95086 is a potential member (probability of 71%). This star is noteworthy as one of the few stars that hosts both a detected debris disc and a directly imaged planet. It has previously only been considered as a potential member of the Lower Centaurus Cr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 72 publications
4
18
0
Order By: Relevance
“…Thus, our empirical approach to estimate the kinematic age of an expanding (as a whole) stellar system by the analysis of the distribution of mutual distances of bona-fide member stars in the past (see, e.g. Booth et al 2021), does not show a global minimum, suggesting also on a possible non-coeval star formation in this extended Cep OB1 association as a complex star forming region unlike to a compact ones (see, e.g., Shevchenko et al 1991). Thus, the estimated ages of Cep OB1 and 4U 2206+54 already are excluding HD 235673 as a birth counterpart owing to the longer flight time (τ = 13.2 +2.0 −0.8 Myr, Sec.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our empirical approach to estimate the kinematic age of an expanding (as a whole) stellar system by the analysis of the distribution of mutual distances of bona-fide member stars in the past (see, e.g. Booth et al 2021), does not show a global minimum, suggesting also on a possible non-coeval star formation in this extended Cep OB1 association as a complex star forming region unlike to a compact ones (see, e.g., Shevchenko et al 1991). Thus, the estimated ages of Cep OB1 and 4U 2206+54 already are excluding HD 235673 as a birth counterpart owing to the longer flight time (τ = 13.2 +2.0 −0.8 Myr, Sec.…”
Section: Discussionmentioning
confidence: 99%
“…Only four 4 known directly imaged planets have nominal masses comparable to or lower than 2M0437b ( 5M JUP ), and all are older: PDS 70 b and c, which orbit a 5 Myr-old star in the Scorpius-Centaurus region (Keppler et al 2018;Haffert et al 2019), 51 Eri b, which orbits a member of the ∼23 Myr-old Beta Pictoris Moving Group (Macintosh et al 2015) and HD 95086b (Rameau et al 2013), with a host star that has been recently re-assigned to the ∼13 Myr-old Carina association (Booth et al 2021). Notably, all the host stars are much more massive than 2M0437.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Torres et al (2008) later re-assessed AB Pic to be a member of Carina, another young moving group (YMG) with age τ ∼ 30 Myr (e.g., Bell et al 2015;Miret-Roig et al 2018). Recently, Booth et al (2021) has revised the age of Carina to be younger and only 13 Myr. Chauvin et al (2005) observed AB Pic to host a planetary-mass companion, AB Pic b, at projected separation 5.…”
Section: Ab Picmentioning
confidence: 99%